Przestępstwo o charakterze terrorystycznym z punktu widzenia obrońcy - Czarny, Bartłomiej (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article focuses on the problem of terrorist offences. The author examines the topic not from the point of view of the doctrine, but from the point of view of practical considerations, especially the application of regulations in judicial practice. He discusses the basic problems that can arise in connection with judicial practice in terrorism-related cases, taking into account the views expressed so far by scholars in the literature referred to in the article.
Keywords: adwokaci; przestępstwo terrorystyczne; prawo karne; zagrożenia bezpieczeństwa